Terpyridine-Based Luminescent Lanthanide Coordination Polymers and Complexes with Various Photophysical Properties - Sedykh, Alexander; Justus Liebig University Giessen (My University, 2023)
This work is focused on using 2,2′:6′,2′′-terpyridines, standalone or in the mixture with other organic ligands, in the investigation of complexes and coordination polymers formation with trivalent rare earth elements and the examination of their properties. 2,2′:6′,2′′-Terpyridines act as a photoluminescence sensitiser in coordination compounds of trivalent lanthanides, increasing the intensity of characteristic 4f-4f metal ion emission. In Chapter 1, an introduction to trivalent lanthanides and their photoluminescence properties is given, as well as known coordination compounds of trivalent rare earth elements with 2,2′:6′,2′′-terpyridine and its derivatives. In Chapter 2, the research goals of this thesis are stated. In Chapter 3, it is described how the swift coordination of 4′-phenyl-2,2′:6′,2′′-terpyridine to trivalent lanthanides and efficient sensitisation of their emission by this ligand were successfully used for their detection with respect to their recovery. The developed process can be used for an urban mining approach, allowing trivalent lanthanide detection at their recoverable concentrations in wastewater and leaching solutions. In Chapter 4, the reactivity of all water-free trichlorides of all rare earth elements (except promethium) with 4′-phenyl-2,2′:6′,2′′-terpyridine is described. The product formation depends on the ionic radii of the metal used, hence, several series of compounds were obtained, from complexes to coordination polymers with a chain formation through anions. In Chapter 5, investigations of the possibility of increasing the dimensionality of products obtained from complexes to coordination polymers through organic N-donor linkers are presented. Various approaches with the introduction of an additional coordination mode were probed by either modifying the 4′-aryl-2,2′:6′,2′′-terpyridine itself or by using a secondary bridging ligand. In Chapter 6, the introduction of the anionic O-donor is presented within the scope of the investigation. Multiple examples of trivalent lanthanide coordination compounds with 2,2′:6′,2′′-terpyridines and O-ligand anions are presented alongside a Eu3+ coordination polymer with 4-([2,2′:6′,2′′-terpyridin]-4′-yl)benzoate. In Chapter 7, tetrameric complexes of Eu3+ and Tb3+ acetates with 4′-phenyl-2,2′:6′,2′′-terpyridine are presented and proposed to be used as solid-state photoluminescence standards due to their stability and suitable emission intensity. This study opens up possible applications of the complexes with regard to quantitative measurements, for example, quantum yield determinations. Altogether, the systematic study of trivalent rare earth elements’ interaction with 2,2′:6′,2′′-terpyridines exposed a remarkable application potential for the trivalent lanthanides recovery as well as for the quantitative photoluminescence standards development.
Keywords: Coordination chemistry; Inorganic chemistry; Lanthanides; ddc:540